The Effect Of Using Comic Media In Social Sciences Subjects On Students' Critical Thinking Abilities - Akhmad Hapis Ansari; Syaharuddin Syaharuddin; Raihanah Sari; Jumriani Jumriani; Fatwa Nur’aini (Program Studi Pendidikan IPS, 2025)
Currently, students are required to have 21st-century skills, and critical thinking skills are one of the important competencies that must be possessed because they shape students to have analytical skills, problem-solving skills, and social awareness in social studies learning. However, the use of media such as comics as a medium for social studies learning in schools is still limited. Based on these conditions, the purpose of this study is to examine the effect of using comics as a medium in social studies lessons on critical thinking skills. This study used a quantitative approach with a non-equivalent control group quasi-experimental research design. The research was conducted at SMPN 2 Alalak. There were two stages of data collection techniques, namely questionnaires and tests. The data analysis techniques applied were descriptive statistics, basic assumptions, and hypotheses. Based on the analysis using SPSS software on the posttest data, a sig. (2-tailed) value of 0.000 < 0.05 was obtained, meaning that H0 was rejected and H1 was accepted, indicating a significant difference between the scores of the experimental and control classes after the treatment. These findings indicate that the use of comic media has a positive effect on improving critical thinking skills. The results of this study are consistent and reinforce the understanding that the use of comic media in social studies learning is not only a visual aid, but also a learning strategy that can encourage active engagement, reflective thinking, and logical decision-making among students. Comic media provide a learning context that is closer to the daily lives of students, making social material more vivid and concrete, and enabling students to build connections between text, images, and the social reality they experience.